2006
DOI: 10.1111/j.1745-6592.2006.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Low‐Cost Waste Material Bagasse Fly Ash in Removing of Cu2+, Ni2+, Zn2+, and Cr3+ from Industrial Waste Water

Abstract: Bagasse fly ash, a waste material generated in the sugar industry, collected from a local sugar firm at Kom‐Umbo district (42 km to the north of the midcity of Aswan), Aswan Governorate, Egypt, was used as a low cost and effective adsorbing surface for the removal of Cu2+, Ni2+, Zn2+, and Cr3+ from industrial waste water. The adsorption capacity was followed as a function of pH, adsorbent dose, metal ion concentration, shaking time, and divers ions. Under the optimum conditions used, more than 95% of some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Testa of Groundnut Shell 18.79 [31] Bagasse fly ash 12.82 [32] Banana peel 6.88 [33] Orange peel 6.01 [33] Tea factory waste 15.26 [34] Eutrophic peat 11.15 [35] Coconut coir pith 24.39 Present study decreased uptake capacities. The Langmuir isotherm was demonstrated to provide the best fit for the equilibrium adsorption data confirming a monolayer adsorption pattern.…”
Section: Adsorbent Q Max (Mg G −1 ) Referencementioning
confidence: 96%
“…Testa of Groundnut Shell 18.79 [31] Bagasse fly ash 12.82 [32] Banana peel 6.88 [33] Orange peel 6.01 [33] Tea factory waste 15.26 [34] Eutrophic peat 11.15 [35] Coconut coir pith 24.39 Present study decreased uptake capacities. The Langmuir isotherm was demonstrated to provide the best fit for the equilibrium adsorption data confirming a monolayer adsorption pattern.…”
Section: Adsorbent Q Max (Mg G −1 ) Referencementioning
confidence: 96%
“…The X-ray spectra of bagasse fly-ash showed the presence of different minerals such as kaolinite, mullite, goethite, α-quartz, γ -alumina, and hematite and the scanning electron microscope (SEM) studies indicated flocs and porous nature of the material. 224 Red mud which is an abundantly available bauxite industry waste is highly alkaline in nature and is principally composed of fine particles of SiO 2 , Al 2 O 3 , Fe 2 O 3 , and TiO 2 and these have been found to be responsible for its high surface reactivity. 225 The surface electrical properties have been found to be dependent on these metal oxides.…”
Section: Inorganic Precursorsmentioning
confidence: 99%
“…EDX spectra of some kaolinite clays have been reported to contain silica and alumina in the range of 54.66 to 63.35% and 22.42 to 25.74% by mass respectively. 60,61 Adsorption results…”
Section: Scanning Electron Micrograph and Electron Dispersive X-ray A...mentioning
confidence: 99%